Marketing of the performing arts : a local perspective. - Cheok, Sharon Eu Kim. (2008)
Our group is inspired to examine the local performing arts industry as we feel that insufficient research is being carried out in this area. In this study, we seek to analyze the performing arts scene in Singapore. Our objective is to gain an insight into consumer’s needs and wants with respect to the performing arts. Interviews conducted with major art organizations allowed us to better understand their trade and what they are providing within constraints.